Study on Marketing of Chrysanthemum Cut Flower With Structure, Conduct, and Market Performance Approach in Cianjur Regency - Endang Saefuddin Mubarok; Siti Munawaroh; Subari; Brahim Abdullah; Rukun Santoso; Ratih Ayu Sekarini (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims at collecting information and analyzing it with respect to the structure, conduct, and market performance of chrysanthemum cut flowers in Cianjur Regency. The research design is descriptively and explanatively quantitative, with multivariate analysis method using 10 reviews. The samples of the research were 72 respondents. Data collection was carried out by interviews, recording and observations.The results of the research indicate that: (1) the market structure belongs to the oligopoly market with CR4 with 85 percent control; (2) each marketing agency performs the same marketing functions but with different behavior; (3) channel one has the highest total margin of 56.52 percent, while channel three has the most efficient margin of 50 percent; (4) in the short term the market at the farmer level and the market at the consumer level are not integrated, but it is integrated in the long term; and (5) the existence of capital cooperation between village collectors encourages an inefficient market and farmers do not have a bargaining position